Aktivitas Anti Helmintik Infusa Biji Pepaya (Carica papaya L.) terhadap Cacing Ascaris Suum (Studi in Vitro) - Edwin Lewis; Hafiz Muchti Kurniawan; Dhanny Jovindho; Andre Budi (Program Studi Farmasi UNAJA, 2023)
Ascaris suum infection remains a significant problem in both veterinary and human health, particularly in areas with poor sanitation. The use of synthetic anthelmintics faces challenges such as resistance and adverse side effects, prompting the search for alternative treatments from natural sources. This study aimed to evaluate the anthelmintic activity of papaya (Carica papaya L.) seed infusion against Ascaris suum through an in vitro approach. Papaya seeds were dried, ground, and extracted using hot water infusion at 90°C. The assay involved immersing A. suum worms in various infusion concentrations (10%, 20%, 30%, and 40%) and observing them at 1, 3, and 6-hour intervals to determine paralysis and mortality times. The results showed that papaya seed infusion exhibited significant concentration- and time-dependent anthelmintic activity. The 40% concentration produced the strongest effect, causing paralysis within 1 hour and mortality within 3 hours. This activity is likely due to the presence of alkaloids, carpaine, flavonoids, and tannins in papaya seeds, which are toxic to the neuromuscular system of the worms. It can be concluded that Carica papaya seed infusion has potential as a natural anthelmintic agent against Ascaris suum.